Maintenance scheduling of generating units in a hydro power system: A case study of EDL region I - P. Netibanedith (2018)
This paper proposes an integrated maintenance scheduling and production planning algorithms for generator maintenance scheduling of a hydro power system. Hydro power station characteristics and constraints are taken into account in maintenance scheduling problem. The studied power system exchanges power with the neighboring country. The objective of this method is to optimize water value or revenue of the hydro power system with standard reliability constraints. The maximum and minimum reservoir operating curves are first determined from hydrology statistics. Then the limited energy of each sub-period is calculated. After that the three step searching is used to find the maximum revenue maintenance schedule. The water value is evaluated according to import and export tariffs. The maximum and minimum reservoir operating curves, the general maintenance constraints and the minimum reliability level are taken into consideration. Based on the proposed method, a computer program is developed and tested with a case study, an existing Electricite Du Laos (EDL) Region I hydro power system. The results confirm the proposed method a better maintenance schedules compared with the maintenance schedule employed by EDL. The system revenue increase of up to 20% is achieved while the reliability is still with in EDL standard.